Temporal Variations among Invasive Pneumococcal Disease Serotypes in Children and Adults in Germany (1992–2008) - Matthias Imöhl; Ralf René Reinert; Mark van der Linden (International Journal of Microbiology)
Nationwide surveillance of invasive pneumococcal disease has been conducted in Germany since 1992. From 1992 to 2008, a total of 12,137 isolates from invasive pneumococcal disease were collected. Data on serotypes were available for 9,394 invasive isolates. The leading serotypes were serotypes 14 (16.5%), 3 (8.0%), 7F (7.6%), 1 (7.3%), and 23F (6.0%). Variations in serotype distribution over the years are particularly extensive, especially concerning serotype 14 (min 7.4%, max 33.5%) with the highest percentages among the isolates serotyped from around 1997 to 2006. Serotypes 1 and 7F increased over the last decade. No increase was observed concerning serotype 19A. Higher pneumococcal conjugate vaccine coverages were observed among children (7v, 57.3%; 10v, 72.8%; 13v, 83.5%) than among adults (7v, 39.9%; 10v, 55.5%; 13v, 73.5%). The temporal variations in serotype distribution have to be kept in mind when interpreting vaccine coverages reported in epidemiological studies.